Ways of formation of onomastic phraseological units (on the material of the Belarusian language) - Leuchanka, Natalia A. (Journal of the Belarusian State University. Philology, 2019)
The paper is devoted to the study of mechanisms of onomastic phraseological units derivation in the Belarusian language. The analysis showed that the most productive way of phraseologism formation is the phraseological-syntactical one. The main methods of renewing the inner form of idioms are metaphor and metonymy. Pseudoproper names are formed due to explication. The main mechanisms of phraseologism formation within the inner phraseological method are estimated. It is established that onomastic phraseological units can be formed as a result of ellipsis of proverbs. It is noted that the formation of phraseological units with the onomastic component is due to linguistic and extralinguistic factors.